Holy Scripture under the Auspices of the Holy Trinity: On John Webster's Trinitarian Doctrine of Scripture. (18th March 2019) - Sanders, Fred
Abstract: As he approached the monumental task of writing his own systematic theology, John Webster gave strategic attention to constructing a doctrine of Scripture that was adequate to support such a project. In contrast to some well‐respected modern systematic theologies that got by with less robust bibliologies (those of Pannenberg and Jenson), Webster saw the need to establish from the outset a more fully elaborated doctrine of Holy Scripture. He framed that doctrine of Scripture by appealing above all to his central dogmatic commitment, the doctrine of the Trinity. The trinitarian contours of Webster's doctrine of Scripture are most conspicuous in his treatment of the missions of the Son and the Spirit. Webster understands the entire Bible as the self‐testimony of the risen Christ (mission of the Son), and explains its cognitive effectiveness in terms of the full range of the work of the Holy Spirit in inspiration and illumination (mission of the Spirit). The trinitarian grounding of his doctrine of Scripture enabled Webster to retrieve the Protestant orthodox doctrine of Scripture's inspiration.